2011
DOI: 10.1002/ajh.21993
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation adherence to deferoxamine and deferasirox in thalassemia

Abstract: The Thalassemia Clinical Research Network collected adherence information from 79 patients on deferoxamine and 186 on deferasirox from 2007 to 2009. Chelation adherence was defined as percent of doses administered in the last 4 weeks (patient report) out of those prescribed (chart review). Chelation history since 2002 was available for 97 patients currently on deferoxamine and 217 on deferasirox, with crude estimates of adherence from chart review. Self-reported adherence to both deferoxamine and deferasirox w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 9 publications
5
51
2
2
Order By: Relevance
“…With adherence to the use of DFO being a major issue in the management of b-thalassemia, 13,49 our results highlight the need for more patient-friendly chelation regimens. The issue, then, is how best to optimize the use of the oral agents.…”
mentioning
confidence: 95%
“…With adherence to the use of DFO being a major issue in the management of b-thalassemia, 13,49 our results highlight the need for more patient-friendly chelation regimens. The issue, then, is how best to optimize the use of the oral agents.…”
mentioning
confidence: 95%
“…It is predicted that these oral medications should provide better overall outcome with chelation therapy compared with DFO due to their ease of use with better compliance [17,18]. Deferasirox, a once-daily oral chelator, showed efficacy with an acceptable safety profile in adult and pediatric populations with up-to 5-year follow up in a large scale prospective clinical studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therein, Gabutti and Piga reported an average adherence of 64% for DFO over a 30-year time horizon, while Weissman et al reported that 62% of persons with thalassemia or SCD were adherent to DFO treatment [27,28]. In more closely-related work comparing patterns of use with DFO and DFX, Trachtenberg et al measured adherence through patient self-reports and medical chart reviews from 2007-2009 among 265 individuals on DFO or DFX [29]. Results for the short-term nonadherence at one month were low, at 8% for DFO and 3% for DFX, though these values worsened with age; comparative results for treatment discontinuations in the current study using claims data were 17% for DFO and 15% for DFX.…”
Section: Cost Analysismentioning
confidence: 99%
“…It is also important to note that persons with SCD have reported significant barriers in access to health care, particularly those associated with delays in treatment [43]. Predictors of nonadherence in SCD remain complex and multifaceted, and current suggestions state that an integrated team approach involving healthcare providers, family caregivers, and treatment centers be utilized to achieve optimal results with chronic therapies [29,42].…”
Section: Cost Analysismentioning
confidence: 99%